ROMANIAN CONSACRATED RECIPES IN THE MILLING AND BAKERY INDUSTRY - Ciprian Nicolae POPA; Radiana Maria TAMBA BEREHOIU; Luminiţa VIŞAN; Vasilica SIMION; Claudia MUREŞAN; Sergiu Erich PALCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Romania has implemented a legislation whose purpose is to recover the recipes of some food products, in their original form, functional before 1984. The original recipes are known as "Romanian consecrated recipes". The purpose of the present study was to evaluate how the producers in the milling and bakery industry complied with this legislation, 5 years after its appearance. Our results show that the number of foods certified as being obtained with "Romanian consecrated recipes" is quite low, only 9 products, of which only 7 can be considered as completely belonging to the bakery industry. Also, the number of producers who hold consecrated recipes certificates is very small (21 producers compared to several thousand who work on the bakery market) and are distributed on less than half of the national territory. The vast majority of applications for consecrated recipes certification are concentrated on bakery products that contain potato derivatives. Only slightly over 18% of the old recipes and technologies are represented in the range of products certified according to the legislation in force. No milling industry product is certified as having consecrated recipes, although there is no equivalent in the products currently available on the market. The products obtained according to "consecrated recipes" have the quality to contribute to the diversified use of the available food resources and to the superior use of some by-products from the industry. However, these types of products are not necessarily correlated with the modern trends in the industry, in terms of energy efficiency or consumer expectations, being not “clean label”.